Conceptualizing dust emission areas and hotspots over the Aeolian landforms via remote-sensing aerosol algorithms (case study: Lake Urmia, a major hypersaline lake in the Middle East) - Hesam Ahmady-Birgani (Geoscience Letters)
Abstract Currently, endorheic saline lakes are rapidly being desiccated worldwide at an alarming rate. Thus, the role of dried-up saline lakebeds in wind erosion and dust emission in the regional climate system and its adjacent environment is poorly understood. Additionally, the term of ‘Hotspot’ in the Aeolian studies, in particular for saline lakes, is somewhat unclear and is perceived differently by scientists. Therefore, this study aimed to conceptualize a new definition of the source areas of Aeolian sand and dust storms. In this regard, some new perceptions entitled ‘Coldspots’, ‘Hotspots’, and ‘Hottestspots’ are introduced via new RS algorithms and ‘Spotfinder’ formula. The present study utilized Google Earth Engine (GEE) to estimate long-term AOD data from MODIS images. The AOD values from the land and marine surfaces at a spatial resolution of 1 km were retrieved by the MAIAC algorithm. The selected saline lake for this study was Lake Urmia, the second largest hypersaline lake in the world, NW Iran. The algorithms of AODNor, AODFrq, and AOD trend are calculated and visualized from 2001 to 2024. Then, using ‘Spotfinder’ quantity and threshold values, the ‘Coldspots’, ‘Hotspots’, and ‘Hottestspots’ are defined and delineated. According to the ‘One Out, All Out’ principle, the ‘Hotspots’ are described as the regions with a high AOD value, high AOD frequency, and an upward AOD trend concurrently, and any reduction or elevation in any one of the feature layer classes would lead to the lower or higher ranks. The findings reveal that 2008 was the onset of hotspots over the eastern shores of Lake Urmia. From 2011 to 2019, the southern and central parts of Lake Urmia were added to areas susceptible to dust emission and wind erosion. Collectively, the ‘Hotspots’ and ‘Hottestspots’ of Lake Urmia are located in the dried-up lakebeds of the shores and bordering areas. The results also show that the dust emission source areas over the Lake Urmia Basin are local and would not be transported long distances. The results of this study have broad implications for decision-makers seeking to know how and where to combat desertification and control sand and dust storms across the dried-up lakebeds of Lake Urmia.